Species-richness in Neotropical Sericothripinae (Thysanoptera: Thripidae) - Lima, Élison Fabrício B.; Mound, Laurence A. (Zootaxa, 2016)
Two of the three recognized genera of Sericothripinae are known from the Neotropics, and 14 new species from this area are here described in this subfamily. Illustrated keys are provided to females of seven species of Hydatothrips, and 41 species of Neohydatothrips, mainly from Brazil but including all recorded species south of the border between Mexico and USA. Plant species on which breeding has been recorded are indicated where possible, notes are provided on the few species of economic importance, and a key is appended to second instar larvae of seven species. Neohydatothrips burungae (Hood) stat. rev. and N. aztecus Johansen stat. rev. are recalled from synonymy with Neohydatothrips signifer (Priesner), and N. denigratus (De Santis) syn. n. is synonymized with N. burungae. Hydatothrips williamsi (Hood) comb. n. is relocated from Neohydatothrips, and as this produces a homonym in the genus, Hydatothrips tareei nom. nov. is proposed for Hydatothrips williamsi Mound & Tree from Australia.